2018
DOI: 10.1097/pcc.0000000000001596
|View full text |Cite
|
Sign up to set email alerts
|

RBC Exposure in Pediatric Extracorporeal Membrane Oxygenation: Epidemiology and Factors Associated With Large Blood Transfusion Volume*

Abstract: Bleeding during extracorporeal membrane oxygenation, frequent laboratory draws, and younger age were associated with increased RBC exposure during extracorporeal membrane oxygenation. Higher transfusion volume was associated with increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Patients often receive blood products to maintain hemoglobin and product targets on ECMO. [50][51][52] In the recent Pediatric Critical Care Transfusion and Anemia Expertise Initiative consensus statements regarding red blood cell transfusion in critical illness, there was insufficient evidence for a specific red blood cell transfusion threshold for children on ECMO, 53 instead recommending transfusion decision-making to take into account evidence of inadequate systemic or regional oxygen delivery, adoption of blood conservation procedures and minimization of donor exposure. 54 Many center protocols maintain hemoglobin between 10-12 g/dl.…”
Section: Blood Product Administrationmentioning
confidence: 99%
“…Patients often receive blood products to maintain hemoglobin and product targets on ECMO. [50][51][52] In the recent Pediatric Critical Care Transfusion and Anemia Expertise Initiative consensus statements regarding red blood cell transfusion in critical illness, there was insufficient evidence for a specific red blood cell transfusion threshold for children on ECMO, 53 instead recommending transfusion decision-making to take into account evidence of inadequate systemic or regional oxygen delivery, adoption of blood conservation procedures and minimization of donor exposure. 54 Many center protocols maintain hemoglobin between 10-12 g/dl.…”
Section: Blood Product Administrationmentioning
confidence: 99%
“…11,31,32 The propensity for neonates on ECMO to suffer from hemolysis may be due to smaller caliber cannulas causing increased shear stress, neonatal red blood cell fragility, and higher transfusion burden. 33,34 It is unclear if the higher rates of hemolysis seen with centrifugal pumps are responsible for other clinical outcomes. In agreement with our findings, other studies have also found an association between higher hemolysis rates and increased in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…If an RBC transfusion started <4 h from the end of a prior transfusion, the two were combined into a single transfusion event. We grouped transfusion events by pre‐transfusion hemoglobin concentration (<10 g/dL, 10‐ < 12 g/dL, and ≥ 12 g/dL), using cutoffs that have been described in prior studies of transfusion in pediatric ECMO populations 9,14–16 . Pre‐transfusion hemoglobin was defined as the most recent level pre‐transfusion, not <1 h and not more than 12 h before the transfusion start time.…”
Section: Methodsmentioning
confidence: 99%